Clients' experiences of one‐to‐one low‐intensity interventions for common mental health problems: An interpretative phenomenological analysis. (29th October 2018) - Amos, Rebekah; Morris, Lydia; Mansell, Warren; Edge, Dawn
Abstract : Objectives: Common mental health disorders such as depression and anxiety are highly prevalent and carry significant health care and economic burdens. The UK's improving access to psychological therapies (IAPT) initiative was developed as a cost‐effective way of reducing the pernicious effects of these disorders. IAPT interventions, such as guided self‐help, have been subjected to considerable quantitative evaluation. However, there has been minimal investigation into clients' experiences of the one‐to‐one low‐intensity interventions (LIIs), which form a key component of IAPT service provision. Qualitative exploration could provide rich data regarding experiences of psychological change and factors affecting therapeutic experiences. This will enable informative, client led insights into how low‐intensity therapy can be improved. Methods: Interpretative phenomenological analysis of eight semi‐structured interviews was used to develop an idiosyncratic understanding of clients' experiences of one‐to‐one LIIs following entry into a randomized control trial (RCT). Results: Four superordinate themes were identified from clients' accounts: goals and expectations of therapy, beneficial aspects of therapy, non‐beneficial aspects of therapy, and the experience of psychological change. A heuristic model of interrelationships between factors is proposed. Conclusions: Both therapeutic techniques and relationships contribute to beneficial therapeutic experiences. The results reported here can be used to inform practice by harnessing the most beneficial aspects of therapy, such as developing adaptive therapeutic approaches to clients' clinical needs and facilitating idiosyncratic processes of psychological change. Due to limited qualitative research in this area, further research should be conducted in different service settings to assess differences and similarities in clients' experiences. Practitioner points: Therapists who adapted to clients' individual needs were perceived as more effective than those who did not. Effective therapeutic experiences were exemplified by a personal therapeutic approach, enough time to discuss issues and normalizing client's experiences. Clients develop idiosyncratic models of change which should be encouraged by therapists over and above clinical models.